Development of PBL-Based Mechanics and Fluids Textbooks Combined with Flipped Classroom to Improve Physics Complex Problem-Solving Skills - Eko Juliyanto; Harsi Admawati (Indonesian Journal of Science and Education, 2024)
In the present and the future, the ability to solve Complex Problems has a role in a person's success in the work environment, community environment and family environment. Although this ability is important, classroom learning has not emphasized the development of complex problem-solving skills. Learning in the classroom still emphasizes the development of static problem-solving skills. This research aims to develop a textbook in the form of a PBL-based e-module combined with Flipped Classroom to be able to improve the ability to solve complex physics problems. In addition, this study also analyzes the validity and effectiveness of the textbook. This type of research is RnD research. The ADDIE RnD model is widely used for the development of teaching materials, the development of learning models and the development of learning media. The ADDIE model was chosen as the development model in this study because it is flexible. The stages of the ADDIE model are Analysis, Design, Development, Implementation, and Evaluation. The results of this study show that the characteristics of Mechanics and Fluids textbooks that are suitable in the application of the PBL model combined with Flipped Classroom to improve Complex Problem Solving skills are a) Deepening the material that is done before the lecture equipped with practice questions; b) Problems presented in the Student Worksheet (LKM) in the textbook in the form of contextual problems; c) Student Worksheets (MFIs) in the textbook involve dynamic situations by utilizing the PhET Simulation application. The results of textbook validation by three validators were categorized as valid with an average score of 4.52 on a scale of 5. The results of the t and Ngain tests showed that the Mechanics and Fluids textbook based on the PBL model combined with the Flipped Classroom was effective in improving the ability to solve complex physics problems.